Digitalisasi Form Laporan Dasa Wisma Kader Posyandu Kenanga di Lingkungan Bekasi Utara - Handayani, Dwipa; Rabbani, Nizar Bagoes; Herdiansyah, Dafa; Saputra, Virga Hendra; Kurnia, Ferdi; Zebua, Yedija Salomo; Wicaksono, Ahmad Bayu; Yazid, Muhammad; Ginting, Brian Permana; Damara, Rian (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Recording Dasa Wisma data at Posyandu Kenanga Taman Wisma Asri is still carried out manually, resulting in inefficiencies in management and the risk of data inaccuracies. Through the Community Service Program (KKN), the digitization of the reporting system was implemented to improve the quality of health and welfare data management. The program involved the development of a Microsoft Excel-based reporting system, including system design, cadre training, and implementation assistance. Program evaluation was conducted through system testing and simulated use with Posyandu cadres. Implementation results showed increased efficiency in data management through a structured recording system. Posyandu cadres demonstrated increased competence in operating the digital system. The program resulted in a significant transformation from manual to digital systems, providing a foundation for the development of a sustainable data management system. Recommendations for future programs include the development of a more comprehensive system and continued training for Posyandu cadres to ensure sustainability of the digital system implementation.